From the formal to the spiritual An investigation into the concepts that illuminate the abstract works of Nena Naguil - Cruz, May Lyn L. (2005)
This thesis investigates the context behind the abstract works of Nena Saguil. It studies the artist's thoughts and perspectives on art that influencedthe kind of works she created. The first part of this thesis presents the personal history of Nena Saguil. It includes her family background, her educationand artistic trainings, affiliations and activities. This section is divided into her Philippine years, from her brith in 1914 until 1954; and her Paris years, from 1954 to her death in 1994. The second part of this thesis presents the artist's works. This section is also divided into the Philippine works and the Paris works. The third part deals with the main objective of this thesis, which is to investigate the artist's frame of mind--the theories, concepts and beliefs she subscribed to--that informed the abstract works she created. In the catalogue of her 1989 retrospective exhibit that featured the abstract works she made beginning 1956, the artist Nena Saguil wrote, "I travel from different parts of the Cosmos to all the corners of the Universe looking for the Absolute." This thesis focuses on illuminating the reasons behind the strong association of the artist and her workswith concepts such as "mystical," "spiritual," "inner necessity," "innerscape," "cosmos," and "transcendence." Although this study leads to an informed appreciation of the artist's works, it does not intend to dictate how these works should be perceived and appreciated.